Evaluating philosophies - Bunge, Mario (Boston Studies in the Philosophy and History of Science, 2012)
Philosophies, whether genuine or spurious, are not usually adopted because of their conceptual, empirical, or moral merits, but because of tradition, political interests, or even temperament-none of which is a good reason. The present book argues for a precise criterion: A philosophy is worth what it helps learn, act, conserve our common heritage, and get along with fellow humans.